Stocktaking methods of facilities in a state of ruin - Drobek, Katarzyna; Szostak, Bartosz; Królikowski, Wojciech (Budownictwo i Architektura / Civil and Architectural Engineering, 2019)
The stocktaking is the basic form of presenting and protecting the object of the historic ruin. It also allows to monitor the behavior state and the degradation progress of an object. Objects in ruin are very specifi c because they usually do not have elements typical for an existing building. This means that in the case of ruins, methods of stocktaking taken in the same way as in the case of traditional facilities will be insuffi cient. Elements of objects in ruin often have complicated and diverse geometry, diffi cult and not completely secure access to all elements. The article presents methods that can be helpful in the stocktaking of such objects. Each method describes the necessary equipment and instruments, the method of taking measurements, accuracy, advantages, and limitations. The paper also presents examples of application for selected methods.